Intelligent Monitoring System Framework for Peatland Management in IoT-Integrated Precision Agriculture - Marleny, Finki Dona; Novriansyah, Irvan; Maulida, Ihdalhubbi; Ansari, Rudy; Mambang, Mambang; Saubari, Nahdi (JOIV : International Journal on Informatics Visualization, 2025)
Peatlands have excellent air retention capabilities and are crucial for environmental health. They act as natural sponges, absorbing and releasing air, which helps maintain soil moisture levels vital for crops. However, peatlands are highly sensitive ecosystems often threatened by unsustainable agricultural practices. When managed sustainably, peatlands scattered across the globe can be utilized for various farming activities. Managing peatlands for food crops presents an alternative to agriculture in peatland areas, enhancing economic growth in rural regions. This research aims to introduce a framework that integrates IoT into the intelligent monitoring of peatland management for precision agriculture. The primary challenge is implementing effective monitoring and management strategies for sensitive peatlands within precision agriculture. The main principle of precision agriculture is data-driven decision-making, supported by modern agricultural management that employs technology and data analysis to optimize farming practices. The proposed system framework can be utilized to identify the best types of food crops for making new decisions while ensuring high yields at the agricultural level. Precision agriculture principles are then applied to enhance the accuracy of monitoring peatland management, focusing on suitable land potential and food crops planted in areas with the highest potential. The results indicate that prioritizing peatlands for food crops reduces inappropriate decisions in selecting food crops. Furthermore, the efficiency of agricultural management can be improved with lower management costs. This framework provides a practical and user-friendly basis for informing all stakeholders on automating Peatland agriculture for food crops using precision agriculture systems integrated with IoT. Management practices that apply information technology aim to optimize crop inputs based on temporal and spatial variability. The cost-effectiveness from this perspective creates transition opportunities for communities, positioning our framework as a solution for designing Peatland management with intelligent monitoring.